The Effect of Green Accounting, Digital Financial Literacy, and Carbon Emission Disclosure on Sustainable Financial Performance - Yanto, Supri; Sari, Putri Irmala; Suryani, Nelly (Ebiz Prima Nusa, 2025)
This study examines the effect of green accounting (GA), digital financial literacy (DFL), and carbon emission disclosure (CED) on sustainable financial performance (SFP) in ISSI-listed companies adopting ESG practices (2019–2023). Using a quantitative approach, panel data from annual reports, sustainability reports, and ESG databases were analyzed via EViews 12, employing moderated regression analysis (MRA) to test interactions. Findings reveal that GA and DFL significantly enhance SFP (β = +, p < 0.05), with CED and firm size acting as positive moderators. The study highlights DFL as a novel driver of SFP in emerging markets, while emphasizing the regulatory role of CED in Indonesia. Limitations include a focus on Sharia-compliant firms, suggesting future research should expand to non-Sharia companies and longitudinal post-2023 data. Practical implications urge policymakers to mandate CED and firms to invest in DFL training. The research contributes originality by integrating GA, DFL, and CED previously unexplored in combination within an ESG framework, offering empirical insights for sustainable finance strategies.